A modular multibody aeroelastic framework for offshore wind turbines - N. Aryan; C. Testa; L. Greco (Ocean Engineering, 2026)

Conference Report: Cerebellar Development and Disease at Single-Cell Resolution - Lena M. Kutscher; Davide Aprile; N. Sumru Bayin; Esther B. E. Becker; Valentina Cerrato; Giacomo Turrini; Marion Coolen; Vincent Cantagrel; Béatrice C. Durand; Myron K. Evans II; Parthiv Haldipur; Kathleen J. Millen; et al. (The Cerebellum, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Association of body mass index with progression from binge-eating behavior into binge-eating disorder among adolescents in the United States: A prospective analysis of pooled data - Abubakr A.A. Al-shoaibi; Jason M. Lavender; Sean J. Kim; Iris Yuefan Shao; Kyle T. Ganson; Alexander Testa; Jinbo He; David V. Glidden; Fiona C. Baker; Jason M. Nagata (Appetite, 2024)

P06-20 OMICs approaches linking effects of endocrine disrupters on developing rat hippocampus with impaired memory function in adult offspring and human stem cell-derived in vitro models - W. Lichtensteiger; C. Bassetti-Gaille; H. Rehrauer; N. Caporale; B. Linillos Pradillo; L. Rancan; H. Idrissi; L. Miguélez-Salas; J. Felix; S.D. Paredes; S. Evangelista; M. de la Fuente; et al. (Toxicology Letters, 2024)

OS04-03 Unravelling the impact of endocrine disruptors on human neurodevelopment through the lens of brain organoids - M. Lessi; N. Caporale; M.T. Rigoli; C. Cheroni; S. Stucchi; G. Matassa; D. Bulgheresi; A. Valenti; G. Testa (Toxicology Letters, 2024)

Physical and Biological Controls on Short-Term Variations in Dissolved Oxygen in Shallow Waters of a Large Temperate Estuary - Jeremy M. Testa; Wei Liu; Walter R. Boynton; Denise Breitburg; Carl Friedrichs; Ming Li; David Parrish; T. Mark Trice; Damian C. Brady (Estuaries and Coasts, 2024)

Noise field properties of marine propellers in open water - C. Testa; F. Porcacchia; R. Muscari; L. Greco (Ocean Engineering, 2023)

Life Cycle Assessment of a system for the extraction and transformation of Waste Water Treatment Sludge (WWTS)-derived lipids into biodiesel - B. Notarnicola; G. Tassielli; P.A. Renzulli; R. Di Capua; F. Astuto; S. Riela; A. Nacci; M. Casiello; M.L. Testa; L.F. Liotta; C. Pastore (Science of The Total Environment, 2023)

Large-Scale Spatial and Temporal Patterns and Importance of Sediment–Water Oxygen and Nutrient Fluxes in the Chesapeake Bay Region - W. R. Boynton; M. A. C. Ceballos; C. L. S. Hodgkins; D. Liang; J. M. Testa (Estuaries and Coasts, 2023)

Simulation of high-frequency dissolved oxygen dynamics in a shallow estuary, the Corsica River, Chesapeake Bay - Richard Tian; Xun Cai; Jeremy M. Testa; Damian C. Brady; Carl F. Cerco; Lewis C. Linker (Frontiers in Marine Science, 2022)
Understanding shallow water biogeochemical dynamics is a challenge in coastal regions, due to the presence of highly variable land-water interface fluxes, tight coupling with sediment processes, tidal dynamics, and diurnal variability in biogeochemical processes. While the deployment of continuous monitoring devices has improved our understanding of high-frequency (12 - 24 hours) variability and spatial heterogeneity in shallow regions, mechanistic modeling of these dynamics has lagged behind conceptual and empirical models. The inherent complexity of shallow water systems is represented in the Corsica River estuary, a small basin within the Chesapeake Bay ecosystem, where abundant monitoring data have been collected from long-term monitoring stations, continuous monitoring sensors, synoptic sensor surveys, and measurements of sediment-water fluxes. A state-of-the-art modeling system, the Semi-implicit Cross-scale Hydroscience Integrated System Model (SCHISM), was applied to the Corsica domain with a high-resolution grid and nutrient loads from the most recent version of the Chesapeake Bay watershed model. The Corsica SCHISM model reproduced observed high-frequency variability in dissolved oxygen, as well as seasonal variability in chlorophyll-a and sediment-water fluxes. Time-series signal analyses using Empirical Model Decomposition and spectral analysis revealed that the diurnal and M2 tide frequencies are the dominant high-frequency modes and physical transport contributes a larger share to dissolved oxygen budgets than biogeochemical processes on an hourly time scale. Heterogeneity and patchiness in dissolved oxygen resulting from phytoplankton distributions and geometry-driven eddies amplify the physical transport effect, and on longer time scales oxygen is controlled more by photosynthesis and respiration. Our simulation demonstrates that interactions among physical and biological dynamics generate complex high-frequency variability in water quality and non-linear reposes to nutrient loading and environmental forcing in shallow water systems.

Long-term Annual Aerial Surveys of Submersed Aquatic Vegetation (SAV) Support Science, Management, and Restoration - Robert J. Orth; William C. Dennison; Cassie Gurbisz; Michael Hannam; Jeni Keisman; J. Brooke Landry; Jonathan S. Lefcheck; Kenneth A. Moore; Rebecca R. Murphy; Christopher J. Patrick; Jeremy Testa; Donald E. Weller; et al. (Estuaries and Coasts, 2022)
Aerial surveys of coastal habitats can uniquely inform the science and management of shallow, coastal zones, and when repeated annually, they reveal changes that are otherwise difficult to assess from ground-based surveys. This paper reviews the utility of a long-term (1984–present) annual aerial monitoring program for submersed aquatic vegetation (SAV) in Chesapeake Bay, its tidal tributaries, and nearby Atlantic coastal bays, USA. We present a series of applications that highlight the program’s importance in assessing anthropogenic impacts, gauging water quality status and trends, establishing and evaluating restoration goals, and understanding the impact of commercial fishing practices on benthic habitats. These examples demonstrate how periodically quantifying coverage of this important foundational habitat answers basic research questions locally, as well as globally, and provides essential information to resource managers. New technologies are enabling more frequent and accurate aerial surveys at greater spatial resolution and lower cost. These advances will support efforts to extend the applications described here to similar issues in other areas.

Simulated Estuary-Wide Response of Seagrass (Zostera marina) to Future Scenarios of Temperature and Sea Level - Cara R. Scalpone; Jessie C. Jarvis; James M. Vasslides; Jeremy M. Testa; Neil K. Ganju (Frontiers in Marine Science, 2020)

Influences of a River Dam on Delivery and Fate of Sediments and Particulate Nutrients to the Adjacent Estuary: Case Study of Conowingo Dam and Chesapeake Bay - Cindy M. Palinkas; Jeremy M. Testa; Jeffrey C. Cornwell; Ming Li; Lawrence P. Sanford (Estuaries and Coasts, 2019)

Nutrient- and Climate-Induced Shifts in the Phenology of Linked Biogeochemical Cycles in a Temperate Estuary - Jeremy M. Testa; Rebecca R. Murphy; Damian C. Brady; William M. Kemp (Frontiers in Marine Science, 2018)

Oxygen and Nutrient Exchanges at the Sediment-Water Interface: a Global Synthesis and Critique of Estuarine and Coastal Data - W. R. Boynton; M. A. C. Ceballos; E. M. Bailey; C. L. S. Hodgkins; J. L. Humphrey; J. M. Testa (Estuaries and Coasts, 2018)

GC–MS characterisation and biological activity of essential oils from different vegetative organs of Plectranthus barbatus and Plectranthus caninus cultivated in north Italy - F. Gelmini; P. Squillace; C. Testa; A.C. Sparacino; S. Angioletti; G. Beretta (Natural Product Research, 2015)

Diazinon and Permethrin Mitigation Across a Grass–Wetland Buffer - M. T. Moore; R. Kröger; M. A. Locke; R. E. Lizotte; S. Testa; C. M. Cooper (Bulletin of Environmental Contamination and Toxicology, 2014)

Cytotoxic activity of Guettarda pohliana Müll. Arg. (Rubiaceae) - Paulo R.N. de Oliveira; Gláucio Testa; Rebeca P. Medina; Cecília M.A. de Oliveira; Lucilia Kato; Cleuza C. da Silva; João E. de Carvalho; Silvana M.O. Santin (Natural Product Research, 2013)

Methamphetamine and lentivirus interactions: Reciprocal enhancement of central nervous system disease - Salvador Huitron-Resendiz; Steven J Henriksen; Margaret C Barr; Maria P Testa; Elena Crawford; Loren H Parsons; Manuel Sanchez-Alavez; Tom R Phillips (Journal of NeuroVirology, 2010)

ULTRASONOGRAPHIC CHARACTERIZATION OF REPRODUCTIVE ANATOMY AND EARLY EMBRYONIC DETECTION IN THE NORTHERN FUR SEAL ( CALLORHINUS URSINUS ) IN THE FIELD - Gregg P. Adams; J. Ward Testa; Caroline E. C. Goertz; Rolf R. Ream; Jeremy T. Sterling (Marine Mammal Science, 2007)

Insulin reduces HBsAg production by PLC/PRF/5 human hepatoma cell line - M. Clementi; I. Testa; P. Bagnarelli; A. Festa; P. Pauri; M. Brugia; L. Calegari; C. de Martinis (Archives of Virology, 1984)